TOPICAL ACTIVITY OF_ Aloe vera (/Lverla ) EXTRACT ON EXCISION WOUND—HEALlNG OF SKIN IN RABBITTS:CLINICAL ANDA HISTOLOGICAL STUDY - A.A..Sawad (Basrah Journal of Veterinary Research)
plant /I/ac van: is a green succulent .cactus-like plant belonging to the lily family ,The.plant has a history of use in folk medicine for skin and otherdisorders. The objective of the study presented in this report was to screen the extracts of this plant for its wound- - healing properties based on its traditional use for wound healing. ethanolic extracts was prepared for topical applications. The dose used was 150 mg/kg daily for 10 days, using the excision wound model in rabbits. Carboxymethyl cellulose (1%) was used as control in . ‘ topical studies. Animals were randomized divided to treatment or control groups, . Wound areas were measured. At the day Il',skin .tissue was excised for histological studies" . Wound areas reduced signiﬁcantly in all treatment groups compared to respective controls (P < .001). Histology outcomes were consistent with changes in the treatment groups. No differences were detected within the treatment groups. The study permits the conclusion that Aloe Vera has wound—hea‘ling potential